Clinical Profile and Outcome in Patients with Coronary Slow Flow Phenomenon. (7th May 2019) - Zhu, Xiaogang; Shen, Hua; Gao, Fei; Wu, Sijing; Ma, Qian; Jia, Shuo; Zhao, Ziwei; Tong, Shan; Zhang, Zhihao; Zhou, Yujie
Abstract : The coronary slow flow phenomenon (CSFP) is a poorly recognized clinical entity characterized by delayed distal vessel opacification in the absence of epicardial coronary stenosis and presently lack of specific data on the clinical profile and outcome. We investigated a cohort of 429 patients who fulfilled the criteria for CSFP to explore the clinical feature, outcome, and risk factor of prognosis. Two teams (clinical center and core lab) were blind to patient data for the assessment of coronary angiograph using corrected thrombolysis in myocardial infarction (TIMI) frame count (CTFC). The study cohort consisted of 429 patients (294 men, 68.5%), aged from 30 to 78 years (mean, 54 years). Two hundred patients (46.6%) out of 429 patients had a history of hypertension, 72 (16.8%) had diabetes mellitus, and 222 (51.7%) had dyslipidemia. All the rates of agreement between two teams in evaluating whether normal flow (CTFC ≤ 27 frames) or slow flow (CTFC > 27 frames) were moderate (0.40 <  κ  < 0.75) for the three arteries. Follow-up (mean, 3.8 years) was done for 421 patients (98.1%). The major adverse cardiovascular events (MACE) occurred in 39 patients (9.3%) out of 421 patients. Multivariate analysis showed that the risk of MACE approximately doubles with age >50 years (hazard ratio (HR) = 2.2, 95% CI: 1.0 to 4.9, andP = 0.042 ), hypertension (HR = 2.1, 95% CI: 1.1 to 4.2, andP = 0.021 ), and dyslipidemia (HR = 2.0, 95% CI: 1.0 to 3.9, andP = 0.042 ). CSFP affects predominantly patients at middle age and above but can occur in any age group; CSFP should be more concerned, particularly in patients >50 years old with hypertension and dyslipidemia.